2012
DOI: 10.1111/j.1600-0625.2012.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact dermatitis: from pathomechanisms to immunotoxicology

Abstract: Contact allergens are small reactive chemicals. They cause allergic contact dermatitis (ACD) by activating the innate and adaptive immune system. Contact allergens are very peculiar because of their built-in autoadjuvanticity that allows them to trigger sterile inflammation following skin penetration. The innate inflammatory response involves the triggering of pattern recognition receptors either by direct chemical interaction with such receptors or by induction of endogenous activators. I discuss here the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 147 publications
(173 reference statements)
0
55
0
3
Order By: Relevance
“…Recent studies have shown clearly that contact allergens have autoadjuvant effects that lead to the efficient activation of the innate immune system, provoking skin inflammation, even in germ-free mice (Martin et al, 2011;Martin, 2012;Kaplan et al, 2012). In addition, they form t-cell epitopes that lead to ACD.…”
Section: Scientific Spin-offs and Premature Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown clearly that contact allergens have autoadjuvant effects that lead to the efficient activation of the innate immune system, provoking skin inflammation, even in germ-free mice (Martin et al, 2011;Martin, 2012;Kaplan et al, 2012). In addition, they form t-cell epitopes that lead to ACD.…”
Section: Scientific Spin-offs and Premature Testsmentioning
confidence: 99%
“…Blocking one of those interconnected pathways interrupts the sensitization process and, in some cases, also prevents elicitation of CHS in successfully sensitized mice. this may result in the development of causative treatments for patients with ACD (Martin et al, 2011;Martin, 2012).…”
Section: Scientific Spin-offs and Premature Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[57][58][59][60] Activated transcription factors, such as nuclear factor kappa B (NF-κ B), activator protein 1 (AP-1), nuclear factor of activated T-cells (NF-AT) and signal transducer and activator of transcription (STAT) factors, induce inflammation and favor the recruitment of CLA + T cells to the skin through chemokines and cell-adhesion molecules (e.g. vascular-cell adhesion molecule 1 and E-selection).…”
mentioning
confidence: 99%
“…The relationship between AD and ACD remains unclear, although AD is characterized by T-helper (Th) cell 2 phenotype in mainly the acute phase, with additional roles for Th1, Th17, and Th22 cells in chronic disease [10]. ACD is being increasingly recognized as a Th17-and Th22-polarized response in addition to a classic Th1 response [11]. Because of the relatively wide overlap of AD and ACD, it is important to include patch testing in the diagnostic battery of physicians caring for children with AD.…”
Section: Introductionmentioning
confidence: 99%